Frequency of Depression in Migraine Patients: A Multicentre Cross-Sectional Study from Pakistan - Madiha Malik, Rabbiyah Masood, Mamoona Tanwir Rana, Sana Fatima, Sana Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Migraine is a debilitating neurological disorder often accompanied by comorbid psychiatric conditions, including depression. However, the prevalence and correlates of depression among migraine patients in Pakistan are under-investigated. Study Objective: This study aimed to estimate the frequency of depression among migraine patients and assess its association with the severity and impact of migraine on daily and professional life. Material and methods: This Cross-sectional study was conducted at the Punjab Institute of Neurosciences (PINS/LGH) in Lahore over a period of 12 months from January to December 2022. A total of 1250 adults aged 18-75 years, diagnosed with migraines based on the International Classification of Headache Disorders, 3rd edition (ICHD-3) criteria, were enrolled. Depression was evaluated using the Urdu version of the Beck Depression Inventory-II (BDI-II). Demographic and clinical data were collected and analyzed. Results: The study reported a significant prevalence of depression among migraine patients, with an observed gender disparity favoring females. Notably, a higher duration and severity of migraines, a greater number of attacks per month, and a profound impact on professional and social life were positively correlated with depression. Practical Implication: significant prevalence of comorbid depression in this particular population, it is imperative to incorporate routine mental health screening as an integral component of standard care protocols. This approach may potentially facilitate early detection and intervention, thereby potentially enhancing overall patient outcomes and quality of life. Conclusion: The high prevalence of depression among migraine patients underscores the need for integrated mental health services within the migraine care paradigm in Pakistan. Regular mental health screening can aid in early detection, facilitating comprehensive management and potentially improving patient outcomes. Keywords: Migraine, Depression, Prevalence, Comorbidity, Mental Health Screening, Pakistan.